Economic development - Nafziger, E. Wayne; Cambridge Books Online (Online service). (Cambridge Cambridge University Press, 2012)
"E. Wayne Nafziger analyzes the economic development of Asia, Africa, Latin America, and East-Central Europe. The book is suitable for those with a background in economics principles. Nafziger explains the reasons for the recent fast growth of India, Poland, Brazil, China, and other Pacific Rim countries, and the slow, yet essential, growth for a turnaround of sub-Saharan Africa. The fifth edition of the text, written by a scholar of developing countries, is replete with real-world examples and up-to-date information. Nafziger discusses poverty, income inequality, hunger, unemployment, the environment and carbon-dioxide emissions, and the widening gap between rich (including middle-income) and poor countries. Other new components include the rise and fall of models based on Russia, Japan, China/Taiwan/Korea, and North America; randomized experiments to assess aid; an exploration of whether information technology and mobile phones can provide poor countries with a shortcut to prosperity; and a discussion of how worldwide financial crises, debt, and trade and capital markets affect developing countries" -- Provided by publisher
"E. Wayne Nafziger analyzes the economic development of Asia, Africa, Latin America, and East-Central Europe" -- Provided by publisher
Preface; Part I. Principles and Concepts of Development: 1. How the other two-thirds live; 2. What is development?; 3. Economic development in historical perspective; 4. Characteristics and institutions of developing countries; 5. Theories of economic development; Part II. Poverty Alleviation and Income Distribution: 6. Poverty, malnutrition, and income inequality; 7. Rural poverty and agricultural transformation; Part III. Factors of Growth: 8. Population and development; 9. Employment, migration, and urbanization; 10. Education, health, and human capital; 11. Capital formation, investment choice, information technology, and technical progress; 12. Entrepreneurship, organization, and innovation; 13. Natural resources and the environment: toward sustainable development; Part IV. The Macroeconomics and International Economics of Development: 14. Monetary, fiscal, and incomes policy, and inflation; 15. Balance of payments, aid, and foreign investment; 16. The external debt and financial crises; 17. International trade; Part V. Development Strategies: 18. The transition to liberalization and economic reform: Eastern Europe, the former Soviet Union, and China; 19. Stabilization, adjustment, and reform
Title from title screen (viewed on November 7, 2023)
Also issued in print format
Mode of access: World Wide Web
Keywords: Income distribution -- Developing countries; Economic development; Developing countries -- Economic conditions